2017
DOI: 10.1021/acsami.7b09218
|View full text |Cite
|
Sign up to set email alerts
|

Deuterohemin-Peptide Enzyme Mimic-Embedded Metal-Organic Frameworks through Biomimetic Mineralization with Efficient ATRP Catalytic Activity

Abstract: An enzyme mimic harboring iron porphyrin (DhHP-6) embedded in zeolite imidazolate framework-8 (ZIF-8) was constructed through a biomimetic mineralization approach to obtain composite DhHP-6@ZIF-8. The composite was then used as a catalyst in the atom transfer radical polymerization (ATRP) of poly(ethylene glycol) methyl ether methacrylate (PEGMA) in which poly(PEGMA) could be synthesized with monomer conversion of 76.1% and M of 45 900 g/mol, stronger than that obtained when using free DhHP-6 as a catalyst. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Supramolecular catalysts have the potential to revolutionize the chemical industry by allowing simpler and more flexible reaction pathways that offers lower cost, reduces the creation of undesired byproducts 16,17,18,19 , operates in a broad range of conditions. 20,21 , and is compatible with renewable and sustainable man-made chemistry. 22,23 Nanocapsule or cage-like supramolecular catalysts have attracted a lot of attention due to their perceived similarities to enzymes and their remarkable efficiencies.…”
mentioning
confidence: 99%
“…Supramolecular catalysts have the potential to revolutionize the chemical industry by allowing simpler and more flexible reaction pathways that offers lower cost, reduces the creation of undesired byproducts 16,17,18,19 , operates in a broad range of conditions. 20,21 , and is compatible with renewable and sustainable man-made chemistry. 22,23 Nanocapsule or cage-like supramolecular catalysts have attracted a lot of attention due to their perceived similarities to enzymes and their remarkable efficiencies.…”
mentioning
confidence: 99%
“…The integration of eROP and enzyme mediated ATRP was a promising environmentally benign process for the preparation of biomaterials. Tang et al later reported the polymerization PEGMA using DhHP-6@ZIF-8 (DhHP-6@ZIF-8 = DhHP-6 embedded in zeolite imidazolate framework-8) as a catalyst and BPN as an initiator [ 139 ]. This catalyst could be applied to the polymerization of PEGA and NIPAAm.…”
Section: The Enzyme Mediated Atrp Systemmentioning
confidence: 99%
“…The embedded or encapsulated DhHP‐6 with the enzyme mimicking ability could boost the activity of the enzyme. The entrapment of DhHP‐6 within the porous shield of ZIF‐8 was confirmed by FT‐IR and PXRD, thus solidfying the strong structural integrity of ZIF‐8 framework which was capable of accomplishing self‐assembly even in the absence of covalent bonding for biomimetic mineralization …”
Section: Mof Cellsmentioning
confidence: 99%